2016
DOI: 10.1093/mnras/stw506
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Gravity rotation curves with a conformal Higgs halo

Abstract: We discuss the effect of a conformally coupled Higgs field on Conformal Gravity (CG) predictions for the rotation curves of galaxies. The Mannheim-Kazanas (MK) metric is a valid vacuum solution of CG's 4-th order Poisson equation if and only if the Higgs field has a particular radial profile, S (r) = S 0 a/(r + a), decreasing from S 0 at r = 0 with radial scale length a. Since particle rest masses scale with S (r)/S 0 , their world lines do not follow time-like geodesics of the MK metric g µν , as previously a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Horne & Marsh [9] and later Beckwith & Sargent [10] have underlined the importance of the velocity gradient on the shape of the global Doppler velocity profile. The point is that different Doppler velocity intervals correspond to regions of the disc having very different areas: for a disc seen edge-on, both the smaller and larger Doppler velocities are found near x=0 and correspond to small areas while large |x| values relate to Doppler velocities close to the rotation velocity at the outer edge of the disc and correspond to large areas.…”
Section: Iii1 Keplerian Shearmentioning
confidence: 99%
“…Horne & Marsh [9] and later Beckwith & Sargent [10] have underlined the importance of the velocity gradient on the shape of the global Doppler velocity profile. The point is that different Doppler velocity intervals correspond to regions of the disc having very different areas: for a disc seen edge-on, both the smaller and larger Doppler velocities are found near x=0 and correspond to small areas while large |x| values relate to Doppler velocities close to the rotation velocity at the outer edge of the disc and correspond to large areas.…”
Section: Iii1 Keplerian Shearmentioning
confidence: 99%
“…In his paper, Horne (2016) examined the effect of the conformally coupled scalar field S(r) in (15) on the rotational curves of galaxies. In particular he showed that when the MK-metric written in the form (14) is stretched to what he calls the "Higgs frame", which is given by…”
Section: The Choice Of Gaugementioning
confidence: 99%
“…In further discussion in his paper, Horne (2016) argues in favor of the metric in the Higgs conformal gauge vis-á-vis gravitational lensing. It has been noted that the γr term in the MK metric produces a negative angle light bending, i.e.…”
Section: Gravitational Lensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This final solution satisfies the vacuum field equations of the 4th order conformal Weyl gravity (CWG). The theory was therefore proposed as an alternative to the dark matter/dark energy scenario [9], and it has been studied from several points of view [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. May or may not being the proper alternative theory to Einstein gravity, the Weyl gravity however exhibits interesting properties.…”
mentioning
confidence: 99%